EARLY PROTEROZOIC TERRANES, COLLISION ZONES, AND ASSOCIATED ANORTHOSITES IN THE NORTHEAST OF THE SIBERIAN CRATON: ISOTOPE GEOCHEMISTRY AND AGE CHARACTERISTICS - Rozen O.M.; Zhuravlev D.Z.; Sukhanov M.K.; Bibikova E.V.; Zlobin V.L. (My University, 2000)
Specific features and evolution of tectonic elements of the ancient continental crust in the northeast of the Siberian craton are discussed on the basis of isotope-geochronological materials. We used data on the exposed basement within the Anabar Shield and Olenek uplift and results of studies of core from deep boreholes and crustal xenoliths in kimberlite pipes together with interpretation of geophysical fields where the basement is overlain by the Riphean-Phanerozoic sedimentary cover. New and earlier Sm-Nd dates are discussed, as well as the results of dating by the U-Pb zircon method, including dating of single grains on a SHRIMP mass spectrometer. The Siberian craton in its northeastern part formed in the Late Paleo-Proterozoic (2.0-1.8 Ga ago) as a result of accretion of Archean microcontinents - granulite-gneiss and granite-greenstone terranes associated along collision fault zones. The juvenile substance of granulite-gneiss terranes (Magan and Daldyn) were separated from the exhausted mantle 3.1 Ga ago, whereas that of granite-greenstone terranes (Birekte and Markha) 2.5-2.4 Ga ago. Primary volcanosedimentary complexes that developed on their basement formed 2.4 Ga ago (Vyurbyur series of granulites of the Magan terrane) and 2.1 Ga ago (Khapchan granulite and Aekit greenschist fold belts of the Birekte terrane).
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой